Analysis of a solar and aerothermal plant combined with a conventional system in an ESCO model in Chile. (July 2016) - Bustos, F.; Lazo, C.; Contreras, J.; Fuentes, A.
Abstract: The work provides technical and economic feasibility studies for solar thermal and aerothermal energy systems for the production of sanitary hot water in large volumes in Chile. The proposed project is based in an Energy Service Company model. Using a particular consumption profile, a sensitivity model has been developed in order to design the aero-solar-thermal system, and to obtain financial indicators. The indicators were applied for both, the company that evaluates the business opportunity, and to their future customers. Also, the model includes an analysis of the reduction of greenhouse emissions and its impact on the project׳s financial performance. A dynamic sensitivity analysis was carried out in order to obtain a probability distribution for the financial results and its risk. Case analysis considered 16 solar collectors, a heat pump of 32 kW for the use of aerothermal energy and a conventional boiler. The set-up allows to obtain an annual solar coverage of 14%. Meanwhile, aerothermal coverage was around 70% and the contribution of the conventional system was 16%. The participation of each subsystem was motivated by a purely financial decision as a result of the sensitivity analysis of the model. On the one hand, a Net Present Value of 35, 600 USD and an Internal Rate of Return of 21% were reached for the client. On the other hand, the Energy Service Company obtained a Net Present Value of 9200 USD and an Internal Rate of Return of 69%. Concerning risk, results indicate that for the customer, there exists a 88% probability to obtain a positive Net Present Value, and for the company this probability is about 70%, obtaining generally positive results. However, sensitivity analysis indicates that there exists high elasticity in some relevant variables such as fuel prices and operational costs which could increase considerably risk to the project.